Jerónimo Martins: bigger is not always better - Mussá, Sultan Taiob (2022)
This is an equity research on Jerónimo Martins Group. A Portugal-based international Group, controlled by SMFS, operating in the Food Distribution, Specialized Retail, and Agribusiness sectors. The Group currently operates in Poland, Portugal, and Colombia, holding a market leadership position in the Polish Food Distribution sector. We performed an analysis of the food retail sector, company drivers and forecasted the company cash-generating ability to assess their current fair value.